Fiscal Policy in Oil Producing Countries During the Recent Oil Price Cycle. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents a detailed analysis of the average fiscal policy responses of oil producing countries (OPCs) to the recent oil price cycle. We find that OPCs worsened their non-oil primary balances substantially during 2003-2008 driven by an increase in primary spending. However, this trend was partially reversed when oil prices went down in 2009. We also find evidence that fiscal policy has been procyclical and has hence exacerbated the fluctuations in economic activity. In addition, we estimate that a small reduction in oil prices could lead to very large financing needs in the near future. Finally, we show that long-term fiscal sustainability positions in OPCs have worsened.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet